Pro-BDNF Knockout Causes Abnormal Motor Behaviours and Early Death in Mice. (1st July 2020) - Li, Hua; Lin, Li-Ying; Zhang, Yan; Lim, Yoon; Rahman, Mehreen; Beck, Andrew; Al-Hawwas, Mohammed; Feng, Shiqing; Bobrovskaya, Larisa; Zhou, Xin-Fu
Highlights: Pro-BDNF KO mouse model established by deleting BDNF pro-domain. BDNF pro-domain KO not only blocks the expression of pro-BDNF but also mBDNF. BDNF pro-domain KO leads to weight loss, abnormal motor behaviours and short lifespan in mice. BDNF pro-domain KO causes apoptotic change in mouse brain. GAD65/67 expression is significantly reduced in pro-BDNF KO mouse brain. Abstract: Brain derived neurotrophic factor (BDNF) is a member of the neurotrophin family, best characterized for its survival and differentiative effects in the central nervous system. Pro-BDNF, known as the precursor of BDNF, is believed to have opposite functions to mature BDNF (mBDNF). The opposing effects of Pro-BDNF and mBDNF have led researchers to propose a 'yin' (Pro-BDNF) and 'yang' (mBDNF) model of which, the specific mechanism of its opposing functions is unclear and requires further investigation. In order to elucidate pro-BDNF's explicit role, we established a pro-BDNF knockout (KO) mouse model. This BDNF pro-domain KO mouse model showed significant weight loss, impaired righting reflex, abnormal motor behaviours and short lifespan (less than 22 days), mimicking a Huntington's disease (HD)-like phenotype. ELISA results showed BDNF pro-domain KO not only blocked pro-BDNF, but also significantly affected the level of mBDNF. Abnormal morphologic changes were found in the dentate gyrus (DG) of the hippocampus in pro-BDNF KO mice, and western blot confirmed significant cell apoptosis in pro-BDNF KO mice brains. Furthermore, the expression of glutamic acid decarboxylase 65/67 (GAD65/67) was significantly reduced in pro-BDNF KO mice, indicating impaired inhibitory neurotransmission. Heterozygous (Het) mice showed impaired learning and memory capability and depressive-like behaviours, compared with wild type (WT) mice. Overall, these results support that pro-domain of BDNF is an indispensable part of the BDNF gene; without the proper formation of pro-BDNF, mBDNF cannot be produced successfully and function correctly on its own. Our study also supports the BDNF hypothesis in the pathogenesis of HD.